(untitled) (Journal of Parents and Teachers, 2015)
Don Bosco presents a Salesian educational project that resides in the combination of education and warmth. The creation of a climate, of a temp values which are based on love, warmth and education, using a teaching method that is based on creating circles of interaction that enable personal growth of the student.